SOME FIXED POINT RESULTS WITH T-DISTANCE SPACES IN COMPLETE B-METRIC SPACES - Ayman Hazaymeh (Journal of Mechanics of Continua and Mathematical Sciences)
In this paper, we present an innovative type of contraction within the framework of T-distance spaces that utilize a b-metric. This advancement allows for the derivation of a new collection of fixed-point results. Additionally, we substantiate our conclusions by offering an illustrative example and showcasing a practical application. Ultimately, we have also derived several fixed-point results that are grounded in our primary findings.